KEPEMIMPINAN KHARISMATIK KYAI DALAM PONDOK PESANTREN MODERN - Ahmad Aditan Fiadha; Suharfani Almaisaroh; Wulan Septy L; Fiddiniyah Qiflunah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract: Leadership is the most important milestone in an organization, educational institution, and country. Leadership is also never stale to be an interesting study material because leadership cannot be separated from human life, as long as there is social interaction between people, there also still exists leadership. Leadership is also a matter of study in aspects of Islamic education, because leadership is very familiar in the Islamic religion. But there was an eccentric which became a hot topic in the topic of Islamic educational leadership about the Kyai’s leadership pattern. The Kyai is often attached to his cult in leadership because his figure is well respected and has supernatural magnets that are able to move a group of people. Kyai is also one of the symbols of the glory pesantren and one of the figures who are closely associated with the development of pesantren. The progress and development of pesantren depends on the strength and greatness of Kyai in managing pesantren. Not a few large boarding schools were born from Kyai who have influence in the environment. But in the dynamics of modern pesantren, these normative traditions seem to erode with time. In this article the author tries to find the pettern of Kyai’s leadership wich in fact in slosely attached to the charismatic and authoritarian leadership patterns in modern boarding schools. And the result wa that the Kyai chose a democratic leadership pattern in leading the modern Islamic boarding school. This is caused by several factors related to the effectiveness of the development of pesantren and the regeneration of leadership relay. Keywords: Leadership, Charismatic, Kyai, Modern Islamic Boarding School Abstrak:Kepemimpinan adalah tonggak terpenting dalam sebuah organisasi, lembaga pendidikan, dan negara. Kepemimpinan juga tidak pernah basi untuk dijadikan bahan kajian yang menarik sebab memang kepemimpinan tidak bisa dipisahkan dari kehidupan manusia, selama masih ada interaksi sosial antar manusia, di situ juga masih tetap eksis kepemimpinan. Kepemimpinan juga menjadi bahan kajian dalam aspek pendidikan Islam, sebab kepemimpinan sangat familiar dalam agama Islam. Namun terjadi keeksentrikan yang menjadi perbincangan hangat dalam topik kepemimpinan pendidikan Islam tentang pola kepemimpinan Kyai. Kyai sering lekat dengan kekultusannya dalam memimpin karena memang figurnya disegani dan memiliki magnet supranatural yang mampu menggerakkan sekelompok orang. Kyai juga salah satu simbol kejayaan pesantren dan salah satu sosok yang erat dengan perkembangan pesantren, maju dan berkembangnya pesantren tergantung dengan kekuatan dan kehebatan Kyai dalam mengelolah pesantren. Tidak sedikit pesantren besar terlahir dari Kyai yang memiliki pengaruh di lingkungannya tersebut. Namun dalam dinamika pesantren modern, tradisi-tradisi normatif tersebut seakan tergerus seiring waktu berjalan. Dalam artikel ini penulis berusaha mencari pola kepemimpinan Kyai yang notabennya lekat dengan pola kepemipinan Kharismatik dan oteriternya dalam pondok pesantren modern. Dan hasilnya adalah Kyai memilih pola kepemimpinan demokratis dalam memimpin pondok pesantren modern. Hal ini disebabkan oleh beberapa faktor terkait kefektifan perkembangan pesantren dan kaderisasi estafet kepemimpinan. Kata Kunci: Kepemimpinan, Kharismatik, Kyai, Pesantren Modern